Corporate Spaniard expatriates: Transnational elite or national globalized elite? - Martín-Cabello, Antonio; García-Manso, Almudena (Política y Sociedad, 2022)
There is some debate about the existence of global elites or national globalized elites. This debate has been developed mostly in a theoretical framework. This article argues that the only way to overcome it is through empirical studies. The paper presents a qualitative research conducted through in-depth interviews to Spaniards corporate expatriates. The results show that there is no clear answer to the initial question. On the one hand, a group of Spaniards corporate expatriates can clearly be seen as global national elite. On the other hand, some have more cosmopolitan features and do not feel so tied to their country of origin.